Observation of cosmic ray anisotropy with GRAPES-3 Experiment. (February 2019) - Mohanty, P K; Ahmad, S; Chandra, A; Dugad, S R; Gupta, S K; Hariharan, B; Hayashi, Y; Jagadeesan, P; Jain, A; Jhansi, V B; Kawakami, S; Kojima, H; et al.
Abstract: Large scale anisotropy of cosmic rays (CRs) in the TeV-PeV energy region has been reported by several experiments located in the Northern Hemisphere as well as by the IceCube, and its surface array IceTop at the South Pole. The GRAPES-3 experiment in Ooty, India is designed to observe CRs in the energy range from a few TeV to over 10 PeV. Its near-equatorial location (11.4°N) provides a unique advantage for observations of CR anisotropy, overlapping with experiments in both the hemispheres. The GRAPES-3 consists of a dense array of ∼400 plastic scintillator detectors spread over an area of 25000 m 2 . It also contains a large area (560 m 2 ) tracking muon detector which provides an excellent capability to discriminate γ-rays against CRs. It has recorded over 10 billion showers since its operation began in 2000. Measurement of CR anisotropy with a subset of this data is presented here.